THE EDUCATIONAL PHILOSOPHY OF AL-FARABI: A LINGUISTIC-PHILOSOPHICAL ANALYSIS OF "VIRTUE", "HAPPINESS", AND "CIVIC ETHICS" - Paltore, Y.; Khoshbateni, H.; Kassymbayev, K. (Journal of Oriental Studies, 2025)
Al-Farabi, one of the foundational thinkers in Islamic philosophy, developed an educational vision deeply rooted in Islamic teachings and influenced by Aristotelian thought. He views the human being as a creation of God, destined to return to Him, and believes that virtue is not innate but acquired through education and conscious effort. Since perfection is not present at birth, it must be cultivated; therefore, education is a central tool for achieving both personal fulfillment and moral excellence. According to Al-Farabi, the path to human happiness involves a clear understanding of what happiness is, a desire to pursue it, and the will to act upon that desire. He distinguishes between two essential methods for developing virtue: ta’dib – تأديب (discipline), which focuses on nurturing intellectual or theoretical virtues, and ta’lim – تعليم (instruction), which supports the growth of ethical and practical virtues. These processes, he argues, must be carried out within a socially guided, morally sound community. Although some aspects of his philosophy may seem idealistic or aspirational, Al-Farabi’s framework emphasizes the transformative power of education and the essential role of society in shaping the virtuous individual. This study examines his classification of virtues, the significance he attaches to civic life, and his belief in the human capacity for moral development. Using textual analysis of primary Arabic sources and comparative insights from Greek and Islamic traditions, the research affirms Al-Farabi’s enduring relevance in contemporary debates on ethics, education, and human potential. Keywords: Al-Farabi, Happiness, Virtue, Education and Training, Islamic Philosophy, Civic Ethics.